Interventional therapy for congenital heart disease: a single centre's experience. (12th October 2011) - Shen, Yongchun; Wen, Fuqiang
Abstract : Objective: To evaluate the efficacy and safety of interventional therapy for patients with congenital heart disease. Methods: The clinical data of 102 cases of congenital heart disease confirmed by echocardiography with computed tomography examination and received interventional therapy were retrospectively analysed, focusing on the efficacy and clinical complications. Results: There were 46 males and 56 females in the age ranged from 6 months to 61 years. The patients distribution included 46 atrial septal defect (ASD) patients, 34 patent ductus arteriosus (PDA) patients, 13 ventricular septal defect (VSD) patients, five pulmonary stenosis (PS) patients, two patients with PDA+ASD, one patient with PDA+VSD and one patient with ASD+PS. The success rate was 98.03% (100/102), two VSD patients occurred haematuria and were recovered after therapy, there were no other obvious complications observed. For patient who received occluder, no residual shunt, no shift or breakage of occlude were observed during the 6 months follow-up. For PS patients, the symptoms were relieved and maintained a good condition. Conclusions: Interventional therapy for congenital heart disease patients is effective and safe. Tran catheter occlusion or balloon dilatation show a promising therapeutic effect on congenital heart disease due to its simple, effective, and rapid recovery features.